Climate Change From a Distance: An Analysis of Construal Level and Psychological Distance From Climate Change - Wang, Susie; Hurlstone, Mark J.; Leviston, Zoe; Walker, Iain; Lawrence, Carmen (Frontiers in Psychology, 2019)
The public perception of climate change as abstract and distant may undermine climate action. According to construal level theory, whether a phenomenon is perceived as psychologically distant or close is associated with whether it is construed as abstract or concrete, respectively. Previous work has established a link between psychological distance and climate action, but the associated role of construal level has yet to be explored in depth. In two representative surveys of Australians (N = 217 and N = 216), and one experiment (N = 319), we tested whether construal level and psychological distance from climate change predicted pro-environmental intentions and policy support, and whether manipulating distance and construal increased pro-environmental behaviours such as donations. Results showed that psychological closeness to climate change predicted more engagement in pro-environmental behaviours, while construal level produced inconsistent results, and manipulations of both variables failed to produce increases in pro-environmental behaviours. In contrast with the central tenet of construal level theory, construal level was unrelated to psychological distance in all three studies. Our findings suggest that the hypothesised relationship between construal level and psychological distance may not hold in the context of climate change, and that it may be difficult to change pro-environmental behaviour by manipulating these variables.